Modifying upconverting nanoparticles with polyelectrolyte multilayers - Palo, Emilia (fi=Turun yliopisto|en=University of Turku|, 2019)
Upconversion luminescence where visible light can be obtained through low energy near-infrared radiation is an interesting research topic especially within the scope of biomedical applications using optical detection. The benefits of using upconverting nanoparticles are low background due to low autofluorescence and narrow bandwidth of lanthanide luminescence. However, their use is still being hampered by the challenges arising from the water based biological matrices. The research for creating hydrophilic nanoparticle surfaces for aqueous environment and simultaneously preventing the quenching of the upconversion luminescence is still ongoing. The aim of the study conducted in this thesis was to produce uniform and highly luminescent upconverting NaYF4:Yb3+,Er3+ nanoparticles suitable for biomedical applications accounting for the challenges of water based matrices. To produce such nanoparticles a synthesis route was modified and selected parameters affecting the nanoparticle structure, size and uniformity were studied and their upconversion luminescence behaviors were measured. To make the upconverting nanoparticles biocompatible, a layer-by-layer approach was chosen for the surface modification method as it has not been studied with upconversion nanoparticles in detail. Two types of bilayer structures in the surface modifications were used, one combining negative polyelectrolytes and positive metal ions and one where both components were polyelectrolytes that could be crosslinked to produce a more rigid bilayer structure. The layer deposition conditions affecting the bilayer structure formation such as polyelectrolyte length, polyelectrolyte concentration, and ionic concentration were studied. The formation of the coating by the layer-by-layer method was confirmed for both bilayer structures and their effect on the upconversion luminescence was studied. It was observed that with the selected coatings and the number of bilayers the obtained upconversion luminescence could be enhanced. The enhancement could be maintained even with five bilayers of coating using additional fluoride during the layer formation. In addition, studies to observe the possible disintegration of the coated upconversion nanomaterials were conducted by both optical and solution concentration methods. It was found that in polyelectrolyte/metal ion coated nanoparticles prepared with selected conditions the emission was maintained in pure water for 24 hours. Crosslinking of the two polyelectrolyte coatings was successful in effectively hindering the fluoride loss from the core nanomaterial. This study demonstrates the usefulness of a widely modifiable layer-by-layer method in the surface modification of upconverting nanoparticles. It offers possibilities to create surface structures where the luminescence and the core particle can be shielded from the deleterious environmental effects while rendering the nanoparticles with functionality for further biomodifications.

Matalaenergisen lähi-infrapunasäteilyn pinoamisen kautta saatava näkyvä valo, eli käänteisviritteinen luminesenssi (upkonversio), on mielenkiintoinen tutkimuskohde optista luentaa käyttävien biolääketieteellisten sovellusten kannalta. Matala mittaustausta sekä lantanidien luminesenssille ominaiset kapeat emissioviivat ovat tällaisten nanokokoisten loisteaineiden suurimmat hyödyt. Paljon vettä sisältävä biologinen ympäristö aiheuttaa kuitenkin merkittäviä haasteita. Luminesenssin sammumisen sekä partikkelien hajoamisen estäminen ovat toistaiseksi ongelmia, joiden ratkaiseminen auttaisi materiaalien laajemmassa hyödyntämisessä. Väitöskirjatyön tarkoituksena oli valmistaa muodoltaan yhtenäisiä ja hyvin loistavia käänteisviritteisiä NaYF4:Yb3+,Er3+ nanopartikkeleita joita voitaisiin hyödyntää biolääketieteellisissä sovelluksissa niiden haasteet huomioiden. Partikkeleiden valmistamista varten muokattiin synteesimenetelmä, jonka valikoituja ominaisuuksia sekä niiden vaikutusta partikkelien rakenteeseen, kokoon ja yhdenmukaisuuteen sekä loisteominaisuuksiin tutkittiin. Kerroskasvatusmenetelmä valittiin pintamuokkausmenetelmäksi koska sillä voitaisiin samaan aikaan tutkia loisteominaisuuksien säilyttämistä, partikkelin hajoamista sekä niiden muokkaamista vesiympäristöön sopivaksi. Menetelmä on myös verrattain vähän käytetty käänteisviritteisten loisteaineiden pintamuokkauksessa. Kerroksia kasvatettiin kahdella tavalla, joko käyttäen negatiivista polyeletrolyyttiä ja positiivista metalli-ionia tai hyödyntäen polyelektrolyyttejä molempina komponentteina, jolloin niiden ketjut voitiin ristisitoa. Eri olosuhteita, kuten polyelektrolyytin pituutta ja pitoisuutta, ionikonsentraatiota sekä näiden vaikutusta kerrosten kasvuun tutkittiin. Molemmilla kerrostustavoilla saatiin kasvatettua haluttu pinta partikkelin pinnalle. Loisteominaisuuksia saatiin parannettua tiettyjä kerrostusolosuhteita käyttäen. Lisäämällä kerrostuksen aikana liuoksen fluoripitoisuutta ja tekemällä ristisidonta kahden polyelektrolyytin välille voitiin parannetut loisteominaisuudet säilyttää jopa viiden kaksoiskerroksen jälkeen. Pinnoitettujen partikkelien hajoamista tutkittiin sekä luminesenssiin perustuvan että fluoriselektiivisen menetelmän avulla. Polyelektrolyytti/metalli-ioni – pinnoitus säilytti näytteen loisteen vedessä 24 ja fosfaattipuskurissa neljä tuntia. Fluorin irtoaminen partikkeleista voitin tehokkaasti estää ristisitomalla kasvatettu polyelektrolyyttipinta. Tutkimus auttaa hyödyntämään laajasti muokattavaa kerroskasvatusmenetelmää ja tarjoaa aiempaa monipuolisempia mahdollisuuksia käänteisviritteisten loistaineiden muokkaukseen. Menetelmän avulla voidaan vähentää ympäristöstä johtuvia ongelmia ja toisaalta tuoda partikkelin pinnalle funktionaalisia ryhmiä myöhempää käyttöä varten.